Soil greenhouse gas dynamics under biosolid amendments based on laboratory, field, and modeling approaches - Khalifah, Shaima; Booker, Lizzie; Wilson, Madison K.; Johnson, Shelby D.; Hutchison, Justin M.; Foltz, Mary E. (Frontiers in Environmental Science, 2025)
The rise in human population and the advent of biological wastewater treatment has led to increased biosolid production, which requires sustainable solutions to mitigate potential negative impacts associated with the disposal of biosolids. Biosolid land application has the potential to decrease reliance on synthetic fertilizers and improve soil fertility; however, the microbial activity and associated greenhouse gas (GHG) emissions need to be evaluated to ensure there are no negative externalities of this approach. To address these issues, this study aimed to (i) assess the potential of a biosolid-amended soil system to emit nitrous oxide (N2O), (ii) quantify actual field GHG emissions from biosolid-amended soils, and (iii) evaluate a process-based model to predict these soil GHG emissions. This study performed a comprehensive analysis, including laboratory (potential assays and gene abundances), field (static chamber GHG measurements), and modeling (process-based) approaches, to understand the effect of biosolids on soil GHG emissions. We found that biosolid application increased soil nitrate and organic matter, and decreased soil pH in the short-term. Together, the changes in soil conditions promoted more denitrification, which became more complete with laboratory potential dinitrogen higher than nitrous oxide as the end-product over time. In the field, GHG emissions were generally higher in biosolid-amended soils, particularly just after biosolid application. While the predictive model was able to simulate general trends for field GHG emissions, it often underpredicted the magnitude of these emissions. Overall, despite initial increases in GHG, biosolids have the potential as a sustainable amendment to improve soil health and mitigate GHG emissions in agricultural practices over the long term. This research contributes to understanding biosolid use in promoting environmental sustainability and offers insights for future agricultural management strategies.